CHALLENGES OF LEARNING ENGLISH AS A FOREIGN LANGUAGE AND THEIR SOLUTIONS - Raxmatova Xakima (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the major challenges faced by learners in studying English as a foreign language and suggests effective solutions to overcome these difficulties. The study focuses on common problems such as limited vocabulary, lack of speaking practice, pronunciation difficulties, grammatical errors, low motivation, and anxiety in communication. The article also analyzes modern teaching approaches, interactive methods, and technological tools that can improve language learning outcomes.